Catalyst for preparing N-methylaniline through continuous catalysis of aniline as well as preparation method and application of catalyst

By using CuOx/CrOy/X catalyst, the problem of low conversion rate and selectivity when catalyzed conversion of aniline to N-methylaniline in the prior art is solved, and high efficiency and good selectivity of N-methylaniline preparation is achieved, and the catalyst has good stability and environmental protection properties.

CN119701984APending Publication Date: 2025-03-28LANZHOU UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411835052.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, when aniline catalytic conversion to N-methylaniline, the conversion rate and selectivity are low, and the catalyst causes corrosion to the equipment, and the by-product N,N-dimethylaniline is produced more frequently.

Method used

The CuOx/CrOy/X catalyst is used, and its copper-chromium molar ratio is Cu:Cr=9:(1-9), and the catalyst is prepared by co-precipitation, impregnation or deposition precipitation method, which is used for the continuous catalytic of aniline.

Benefits of technology

High conversion rate (up to 99%) and high selectivity of aniline (up to 99%) are achieved, while reducing the generation of by-products, and the catalyst remains stable during long-term use, reducing equipment energy consumption and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005186468050000081
    Figure BDA0005186468050000081
  • Figure BDA0005186468050000091
    Figure BDA0005186468050000091
Patent Text Reader

Abstract

The invention provides a catalyst for preparing N-methylaniline through continuous catalysis of aniline as well as a preparation method and application of the catalyst, and relates to the technical field of synthesis of N-methylaniline. The catalyst is recorded as CuOx / CrOy / X, the catalyst is used in the process of preparing N-methylaniline through continuous catalysis of aniline, the problems of low conversion rate and selectivity of conversion from aniline to N-methylaniline through catalysis in the prior art are solved, and the final conversion rate of aniline and the selectivity of N-methylaniline can reach 99%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of N-methylaniline synthesis, and in particular to a catalyst used for continuous catalytic preparation of N-methylaniline from aniline, and a preparation method and application thereof. Background Art

[0002] N-methylaniline, the N-methylation product of aniline, is a very important organic intermediate and is widely used in the production of chemical industrial products such as pesticides, medicines, dyes and other fine chemicals. The synthesis methods of N-methylaniline are divided into liquid phase synthesis method and gas phase synthesis method.

[0003] The traditional liquid phase synthesis method uses aniline as raw material, methanol as methylation agent, and sulfuric acid as catalyst to catalytically convert aniline into N-methylaniline, and removes unreacted aniline, methanol, N,N-dimethylaniline and water by distillation to obtain the finished N-methylaniline. However, the above method has the problem of not being able to generate N-methylaniline with high selectivity, and the catalyst will cause great corrosion to the reaction equipment, so it has been eliminated by most manufacturers.

[0004] Patent 201910767498.7 provides a method using water-soluble transition metal iridium as a catalyst. Under relatively mild conditions, by mixing aniline, methanol, water and alkali, a monomethylated product can be obtained with a yield of up to 80%. The traditional gas phase synthesis method uses a mixed liquid of aniline and methanol as a raw material, introduces the raw material into the reactor through gasification, and reacts under the action of a solid catalyst. The reaction is generally carried out at normal pressure, and the reaction temperature is usually controlled in the range of 200 to 250 ° C. The disadvantage of this method is that the conversion rate of aniline during the reaction is low, so it is particularly important to develop a catalyst that can achieve high conversion rate, high selectivity and long-term stable operation.

[0005] Although a series of catalysts have been developed based on this reaction, which have performed well in improving the conversion rate of aniline, they still need to be improved in improving the selectivity of N-methylaniline. For example, the copper-zinc catalyst described in patent 202111431091.0 can achieve a maximum conversion rate of 99% for aniline at a higher temperature, but the selectivity of N-methylaniline produced is only 9-90%, and a certain amount of N,N-dimethylaniline by-products is also produced. In addition, in order to achieve high conversion rate and high selectivity, there is also a method of synergistically catalyzing aniline to N-methylaniline by adding more metals. For example, the copper-zinc-chromium-aluminum spinel catalyst described in patent 201710299685.8 can increase the single-pass conversion rate of aniline to more than 90%, while increasing the selectivity of N-methylaniline to more than 98%. Therefore, the research and development of catalysts with both high aniline conversion rate and high N-methylaniline selectivity is particularly important for the further development of the industry. Summary of the invention

[0006] The purpose of the present invention is to provide a catalyst and a preparation method and application thereof. The catalyst is used in the process of continuously catalyzing the preparation of N-methylaniline from aniline, overcoming the problems of low conversion rate and selectivity of the existing catalytic conversion of aniline to N-methylaniline. The final conversion rate of aniline and the selectivity of N-methylaniline can both reach 99%.

[0007] The catalyst of the present invention is CuOx / CrOy / X, wherein the molar ratio of copper to chromium is Cu:Cr=9:(1-9).

[0008] Furthermore, the molar ratio of copper to chromium is Cu:Cr=2:(1-5).

[0009] Furthermore, X is a carrier, and the carrier is one or more of Al2O3, SiO2, ZrO2, and TiO2.

[0010] The invention provides a preparation method of the catalyst including a co-precipitation method, an impregnation method and a deposition precipitation method.

[0011] The coprecipitation preparation method of the catalyst of the present invention comprises the following steps:

[0012] S11, preparing a mixed precursor solution and a precipitant aqueous solution;

[0013] S12, dropping the precipitant aqueous solution into the mixed precursor solution at a rate of 1 to 2 drops / s to perform co-precipitation;

[0014] S13, drying and calcining the obtained precipitate to obtain a CuOx / CrOy / X catalyst.

[0015] Furthermore, the metal precursor solution is composed of a Cu precursor solution, a Cr precursor solution and a carrier precursor solution.

[0016] Furthermore, the precursor is one or more of nitrate, oxynitrate, acetate, halide, sulfate

[0017] Furthermore, the concentration of the mixed precursor solution is 0.01-2 mol / L.

[0018] Furthermore, the precipitant is one or more of ammonia water, ammonium carbonate, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, sodium hydroxide, and potassium hydroxide.

[0019] Furthermore, the concentration of the precipitant aqueous solution is 0.1-3 mol / L.

[0020] Furthermore, the coprecipitation temperature is 40° C. to 70° C., and the heating condition is an oil bath.

[0021] Furthermore, the coprecipitation pH is 6-10.

[0022] Furthermore, the drying temperature is 60°C to 80°C.

[0023] Furthermore, the calcination temperature is 300° C. to 500° C., the calcination time is 2 to 6 hours, and the calcination is carried out in an air atmosphere.

[0024] The impregnation method for preparing the catalyst of the present invention comprises the following steps:

[0025] S21, mixing the catalyst carrier with water and stirring to obtain a mixture A;

[0026] S21, mixing the metal precursor with water and stirring to dissolve, to obtain a mixture B;

[0027] S23, adding the mixture B into the mixture A, and performing an immersion treatment under stirring;

[0028] S24, rotary evaporating the impregnated catalyst to dryness, and then drying and calcining the catalyst to obtain a CuOx / CrOy / X catalyst.

[0029] Furthermore, the weight-to-volume ratio of the catalyst carrier to water is 1 g: (4-10) mL.

[0030] Furthermore, the weight-to-volume ratio of the metal precursor to water is 1 g:(4-10) mL.

[0031] Furthermore, the metal precursor is one or more of nitrate, oxynitrate, acetate, halide, and sulfate.

[0032] Furthermore, the immersion treatment time is 6 hours.

[0033] Furthermore, the drying temperature is 80° C. and the drying time is 12 hours.

[0034] Furthermore, the calcination temperature is 350° C., the calcination time is 3 hours, and the calcination is carried out in an air atmosphere.

[0035] The catalyst preparation method of the present invention comprises the following steps:

[0036] S31, mixing the catalyst carrier with water and stirring to obtain a mixture A;

[0037] S32, adding a metal precursor to mixture A to obtain mixture B;

[0038] S33, adding Na2CO3 aqueous solution dropwise to the mixture B under stirring until the pH value of the solution is 7-8, and stopping stirring after the addition is completed to obtain a precipitated mother solution;

[0039] S34, filtering the precipitated mother liquor after aging, and washing with deionized water;

[0040] S35, drying and calcining the washed precipitate to obtain a CuOx / CrOy / X catalyst.

[0041] Furthermore, the weight-to-volume ratio of the chemical carrier to water is 1 g: (4-10) mL.

[0042] Furthermore, the weight ratio of the metal precursor to the catalyst carrier is 1 g: (4-10) mL.

[0043] Furthermore, the metal precursor is one or more of nitrate, oxynitrate, acetate, halide, and sulfate.

[0044] Furthermore, the heating temperature of the mixture B is 60° C., and the heating method is an oil bath.

[0045] Furthermore, the concentration of the Na2CO3 aqueous solution is 0.1 to 3 mol / L.

[0046] Furthermore, the stirring speed is 600 r / min.

[0047] Furthermore, the aging temperature is 60° C. and the aging time is 12 hours.

[0048] Furthermore, the drying temperature is 80° C. and the drying time is 12 hours.

[0049] Furthermore, the calcination temperature is 350° C., the calcination time is 3 hours, and the calcination is carried out in an air atmosphere.

[0050] The present invention provides three different catalyst preparation methods, among which, the co-precipitation method: using a precipitant to uniformly precipitate Cu and Cr precursors onto a carrier; or without a carrier, Cu, Cr and the carrier are prepared by co-precipitation in a certain ratio by using a precipitant; the impregnation method: in a solution, the Cu and Cr precursors are fully stirred and mixed with the carrier, and the elements are directly deposited on the carrier by rotary evaporation; the deposition precipitation method: the Cu and Cr precursors are mixed with the carrier to form a suspension, and the metal elements are precipitated by controlling the pH.

[0051] Another object of the present invention is to provide the use of the catalyst in the continuous catalytic preparation of N-methylaniline from aniline, comprising the following steps:

[0052] S41, take an appropriate amount of quartz wool pad in the middle of the quartz tube, fill 2g of quartz sand on the top of the quartz wool as the lower part of the catalyst bed, then evenly fill 0.5g of catalyst mixed with 3g of quartz sand on the top as the middle part of the catalyst bed, and finally fill 2g of quartz sand on the top as the upper part of the catalyst bed to complete the filling of the catalyst bed of the fixed bed reactor;

[0053] S42, using a fixed bed continuous flow reactor to carry out N-methylation reaction of aniline, and after the reaction product flows through a condensation tank to be condensed, collecting the liquid product;

[0054] The catalyst is subjected to in-situ activation treatment before the reaction, and the treatment method is as follows:

[0055] The catalyst was placed in a 5% (v / v) H2 / Ar atmosphere and maintained at 250°C to 350°C for 3 to 5 hours.

[0056] Furthermore, the particle size of the quartz sand is 40 to 80 meshes;

[0057] Furthermore, the N-methylation reaction temperature of aniline is 100°C to 400°C, the reaction pressure is 0.1 to 4 MPa, and the mass space velocity of aniline is 0.45 to 0.9 h -1 Preferably, the N-methylation reaction temperature of aniline is 160°C to 280°C.

[0058] Compared with the prior art, the present invention has the following beneficial effects:

[0059] The N-methylaniline fixed bed production process provided by the invention not only significantly reduces equipment energy consumption and reduces production costs, but also the catalyst still has good stability after continuous reaction for 1000h without obvious deactivation. In addition, due to the high selectivity of the catalyst, aniline is almost completely converted into N-methylaniline without the generation of by-products. This enables the present invention to achieve the continuous catalytic conversion of aniline and efficiently produce N-methylaniline. Compared with traditional catalytic methods, the catalyst of the present invention has higher conversion rate and selectivity, lower energy consumption and longer service life, and has brought huge economic benefits and environmental benefits to industrial production. DETAILED DESCRIPTION

[0060] The technical solution provided by the present invention is further described below in conjunction with embodiments.

[0061] Example 1

[0062] Weigh 13.78g Cu(NO3)2·3H2O, 14.03g Cr(NO3)3·9H2O and 14.27gAl(NO3)3·9H2O were prepared into 200mL aqueous solution and placed in a 1000mL round-bottom flask. 15.59gNa2CO3 was weighed and prepared into 200mL aqueous solution. The metal precursor solution was placed in a 60℃ oil bath stirring pot and the stirring speed was set to 600r / min. The prepared Na2CO3 solution was dripped into the metal precursor solution using a dropping funnel at a dripping speed of about 1 to 2 drops / s. When the Na2CO3 solution was consumed, the stirring was stopped. The obtained precipitate mother liquor was aged in a 60℃ oil bath pot for 12h, cooled and vacuum filtered. After filtration, the precipitate was transferred to a 500mL beaker and washed with deionized water with stirring for 30min. The filtration and washing steps were repeated 3 times. The final precipitate was placed in an 80℃ oven for drying for 12h. The dried precipitate was placed in a crucible and calcined in air at 350℃ for 3h to obtain a catalyst oxidation state precursor. Finally, the pellets were pressed at 30 MPa, crushed, and screened to 40-80 mesh for evaluation.

[0063] Weigh 0.5 g of the screened catalyst into a quartz reaction tube with an inner diameter of 14 mm, reduce it at 300 ° C for 3 h in a 5% (v / v) H2 / Ar atmosphere at normal pressure, then introduce argon gas, and react at normal pressure, 200 ° C, LHSV (AN) = 0.45 h -1 The reaction activity was evaluated under the following conditions. After the reaction product was condensed in the condensation tank, the liquid product was collected, and sampling and analysis were performed every 8 hours. GC-MS was used for qualitative analysis, and Agilent GC-8890 was used for quantitative analysis.

[0064] Example 2

[0065] Weigh 13.78g Cu(NO3)2·3H2O and 11.29g Cr(NO3) 3· 5gH2O and 14.27gAl(NO3)3·9H2O were prepared into 200mL aqueous solution and placed in a 1000mL round-bottom flask. The remaining process steps and parameters as well as the catalyst evaluation method were the same as those in Example 1.

[0066] Example 3

[0067] 15.33 g Ni(NO3)2·6H2O, 14.03 g Cr(NO3)3·9H2O, and 14.27 g Al(NO3)3·9H2O were weighed to prepare 200 mL aqueous solution and placed in a 1000 mL round-bottom flask. The remaining process steps and parameters as well as the catalyst evaluation method were the same as in Example 1.

[0068] Example 4

[0069] Weigh 5.0g of γ-Al2O3 carrier into a 100mL eggplant-shaped bottle and add 20mL of deionized water, stir; weigh 5.7g of Cu(NO3)2·3H2O and 7.2g of Cr(NO3)3·9H2O and dissolve them in a round-bottom flask containing 30mL of deionized water, stir and dissolve, add them to the eggplant-shaped bottle after dissolution, and continue stirring for 6h. After stirring, perform rotary evaporation until all water is dried. Transfer the solid to a watch glass, place it in an 80℃ oven for 12h, place the dried precipitate in a crucible and roast it in air at 350℃ for 3h to obtain the catalyst oxidation state precursor. Finally, press the tablets at 30MPa, crush them, and screen 40-80 mesh for evaluation.

[0070] Weigh 0.5g of the screened catalyst and load it into a quartz reaction tube with an inner diameter of 14mm. Reduce it in pure H2 at 300℃ for 3h at normal pressure, then introduce the carrier gas. The reaction is carried out at normal pressure, 200℃, LHSV(AN)=0.45h -1 The reaction activity was evaluated under the following conditions.

[0071] Example 5

[0072] Weigh 5.0 g of γ-Al2O3 carrier into a 100 mL eggplant-shaped bottle and add 20 mL of deionized water, stir. Weigh 1.9 g of Cu(NO3)2·3H2O and 2.4 g of Cr(NO3)3·9H2O and dissolve them in a round-bottom flask filled with 30 mL of deionized water. The remaining process steps and parameters and the evaluation method of the catalyst are the same as those in Example 4.

[0073] Example 6

[0074] Weigh 5.0 g of γ-Al2O3 carrier into a 100 mL eggplant-shaped bottle and add 20 mL of deionized water, and stir; weigh 9.5 g of Cu(NO3)2·3H2O and 12.0 g of Cr(NO3)3·9H2O and dissolve them in a round-bottom flask filled with 30 mL of deionized water. The remaining process steps and parameters and the evaluation method of the catalyst are the same as those in Example 4.

[0075] Example 7

[0076] Weigh 10 g of SiO2 carrier into a 1000 mL round-bottom flask and add 200 mL of deionized water. Weigh 13.78g of Cu(NO3)2·3H2O and 14.03g of Cr(NO3)3·9H2O and add them to a round-bottom flask, weigh 12.64g of Na2CO3 to prepare a 200mL aqueous solution, place the metal precursor solution in a 60°C oil bath stirring pot, set the stirring speed to 600r / min, and use a dropping funnel to drop the prepared Na2CO3 solution into the metal precursor solution at a dropping speed of about 1 to 2 drops / s. When the Na2CO3 solution is consumed, stop stirring, and age the resulting precipitate mother liquor in a 60°C oil bath pot for 12h, cool and then perform vacuum filtration. After filtration, transfer the precipitate to a 500mL beaker, stir and wash with deionized water for 30min, repeat the filtration and washing steps 3 times, and finally place the resulting precipitate in an 80°C oven for 12h of drying. The dried precipitate is placed in a crucible and calcined in air at 350°C for 3h to obtain a catalyst oxidation state precursor. Finally, the pellets were pressed at 30 MPa, crushed, and screened to 40-80 mesh for evaluation.

[0077] Weigh 0.5g of the screened catalyst and load it into a quartz reaction tube with an inner diameter of 14mm. Reduce it in pure H2 at 300℃ for 3h at normal pressure, then introduce the carrier gas. The reaction is carried out at normal pressure, 200℃, LHSV(AN)=0.45h -1 The reaction activity was evaluated under the following conditions.

[0078] Example 8

[0079] 10 g of ZrO2 carrier was weighed into a 1000 mL round-bottom flask, and 200 mL of deionized water was added. 13.78 g of Cu(NO3)2·3H2O and 14.03 g of Cr(NO3)3·9H2O were weighed into the round-bottom flask. The remaining process steps and parameters and the evaluation method of the catalyst were the same as those in Example 7.

[0080] Example 9

[0081] 10 g TiO2 carrier was weighed into a 1000 mL round-bottom flask, and 200 mL deionized water was added. 13.78 g Cu(NO3)2·3H2O and 14.03 g Cr(NO3)3·9H2O were weighed into the round-bottom flask, and the remaining process steps and parameters as well as the catalyst evaluation method were the same as those in Example 7.

[0082] Example 10

[0083] Same as Example 1, except that the reaction temperature is 180°C.

[0084] Embodiment 11

[0085] Same as Example 1, except that the reaction temperature is 220°C.

[0086] Example 12

[0087] Same as Example 1, except that the reaction temperature is 240°C.

[0088] Example 13

[0089] Same as Example 1, except that: LHSV(AN)=0.9h -1 .

[0090] Embodiment 14

[0091] Same as Example 1, except that: LHSV(AN)=0.78h -1 .

[0092] Embodiment 15

[0093] Same as Example 1, except that: LHSV(AN)=0.72h -1 .

[0094] Example 16

[0095] Same as Example 1, except that: LHSV(AN)=0.66h -1 .

[0096] Embodiment 17

[0097] Same as Example 1, except that the reaction pressure is 1 MPa.

[0098] Embodiment 18

[0099] Same as Example 1, except that the reaction pressure is 2 MPa.

[0100] Embodiment 19

[0101] Same as Example 1, except that the reaction pressure is 4 MPa.

[0102] Embodiment 20

[0103] The catalyst prepared in Example 1 was selected for stability test, and a fixed bed reactor was used for continuous feeding reaction, and the reaction solution was taken for analysis of sample components at intervals of 6 to 8 hours, and the operation was continuous for 1000 hours. Sampling analysis was performed after 1000 hours of operation. Upon testing, the aniline conversion rate was 98.7%, and the N-methylaniline selectivity was 96.3%. By comparison, after 1000 hours of continuous use, the aniline conversion rate and the N-methylaniline selectivity of the catalyst of the present invention only slightly decreased. It can be seen that the catalyst still has good stability after 1000 hours of continuous reaction, and there is no obvious deactivation phenomenon.

[0104] Comparative Example 1

[0105] The catalyst preparation method is the same as that in Example 1, except that the catalyst activation method is different.

[0106] Specifically, 0.5 g of the screened catalyst was weighed and loaded into a quartz reaction tube with an inner diameter of 14 mm, and the catalyst was activated using methanol vapor. The catalyst evaluation method was the same as in Example 1.

[0107] Experiments have shown that in the present invention, water will reform with methanol, and water is also easy to cause sintering of Cu catalysts. Therefore, the catalytic effect is not ideal.

[0108] Comparative Example 2

[0109] The catalyst preparation method is the same as that in Example 1, except that the catalyst is not subjected to pre-reduction treatment.

[0110] Specifically, 0.5 g of the screened catalyst was weighed and loaded into a quartz reaction tube with an inner diameter of 14 mm, and argon was directly introduced. The reaction was carried out at normal pressure, 200° C., and LHSV (AN) = 0.45 h -1 Reaction activity was evaluated under

[0111] The aniline conversion rate of the catalysts of the present invention and the comparative example and the selectivity of N-methylaniline, N,N-dimethylaniline and N-methylformaniline are as follows:

[0112]

[0113]

[0114] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of ​​the present invention. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A catalyst for the continuous catalytic preparation of N-methylaniline from aniline, characterized in that: The catalyst is CuOx / CrOy / X, wherein the molar ratio of copper to chromium is Cu:Cr=9:(1-9).

2. The catalyst according to claim 1, characterized in that The X is a carrier, and the carrier is one or more of Al2O3, SiO2, ZrO2, and TiO2.

3. The method for preparing the catalyst according to claim 1 or 2, characterized in that: Including co-precipitation method, impregnation method, and sedimentation precipitation method.

4. Use of the catalyst according to claim 1 or 2 in the continuous catalytic preparation of N-methylaniline from aniline, characterized in that: The following steps are involved: S41, take an appropriate amount of quartz wool pad in the middle of the quartz tube, fill 2g of quartz sand on the top of the quartz wool as the lower part of the catalyst bed, then evenly fill 0.5g of catalyst mixed with 3g of quartz sand on the top as the middle part of the catalyst bed, and finally fill 2g of quartz sand on the top as the upper part of the catalyst bed to complete the filling of the catalyst bed of the fixed bed reactor; S42. A fixed bed continuous flow reactor is used to carry out N-methylation reaction of aniline. After the reaction product flows through a condensation tank and is condensed, the liquid product is collected.

5. The use according to claim 4, characterized in that: The catalyst is subjected to in-situ activation treatment before the reaction, and the treatment method is as follows: The catalyst was placed in a 5% (v / v) H2 / Ar atmosphere and maintained at 250°C to 350°C for 3 to 5 hours.

6. The use according to claim 4, characterized in that: The N-methylation reaction temperature of aniline is 100° C. to 400° C., the reaction pressure is 0.1 to 4 MPa, and the mass space velocity of aniline is 0.45 to 0.9 h -1 .

Citation Information

Patent Citations

  • Preparation method of catalyst for synthesis of N-methylaniline and application

    CN107115881A

  • Method for synthesizing N-methylaniline in water

    CN112409186A

  • Copper-zinc catalyst for preparing N-methylaniline and N,N-dimethylaniline as well as preparation method and application of copper-zinc catalyst

    CN113976128A

  • Method for synthesizing N-arylalkylamine compound

    CN101792393A

  • Catalyst for preparing N-methylaniline and method for preparing N-methylaniline

    CN118847123A